Differential prognostic impact of GELTAMO‐IPI in cell of origin subtypes of Diffuse Large B Cell Lymphoma as defined by the Hans algorithm. (5th July 2018) - Montalbán, Carlos; Díaz‐López, Antonio; Martín, Alejandro; Baile, Mónica; Sanchez, José M.; Sancho, Juan M.; García, Olga; Novelli, Silvana; Monter‐Rovira, Anna; Salar, Antonio; Bastos, Mariana; Gutiérrez, Antonio; et al.
Summary: The Grupo Español de Linfomas y Trasplantes de Médula Ósea International Prognostic Index (GELTAMO‐IPI) stratifies four risk groups in diffuse large B cell lymphoma (DLBCL) patients treated with immunochaemotherapy: low (LR), low‐intermediate (LIR), high‐intermediate (HIR), and high (HR). The present study explores the effect of GELTAMO‐IPI in the DLBCL subtypes defined by the immunohistochaemistry‐based Hans algorithm, Germinal Centre B (GCB) and non‐GCB. A multivariate Cox regression model including GELTAMO‐IPI risk groups, cell of origin (COO) subtypes and their product was developed to evaluate interaction between the two variables. The COO subtype was available in 839 patients (380 GCB; 459 non‐GCB) and both the GELTAMO‐IPI and the COO subtype in 780 (353 GCB; 427 non‐GCB). There were no differences in 5‐year overall survival (OS) between the two subtypes. The Cox model revealed interaction between the GELTAMO‐IPI risk groups and the COO subtypes ( P = 0·005), indicating that GELTAMO‐IPI has a different effect in the two subtypes. Three risk groups were stratified in both COO subtypes: in the GCB subtype, LR, LIR and the combined HIR+HR had 5‐year OS of 100%, 75% and 52%, respectively. In the non‐GCB subtype, LR, the combined LIR+HIR and HR had a 5‐year OS of, 97%, 82% and 35% respectively. GELTAMO‐IPI identifies a genuine poor outcome group of patients in the DLBCL non‐GCB subtype.